"Synthesis, structural, photophysical and electrochemical studies of various d-metal complexes of btp [2,6-bis(1,2,3-triazol-4-yl)pyridine] ligands that give rise to the formation of metallo-supramolecular gels" - GUNNLAUGSSON, THORFINNUR; BOLAND, JOHN (My University, 2014)
2,6-Bis(1,2,3-triazol-4-yl)pyridine (btp) is a terdentate binding motif that is synthesised modularly via the CuAAC reaction. Herein, we present the synthesis of ligands 1 and 2 and the investigation of the coordination chemistry, photophysical behaviour and electrochemistry of complexes of these with a number of d-metal ions (e.g. Ru(II), Ir(III), Ni(II) and Pt(II)). The X-ray crystal structures of ligand 1 and the complexes [Ru·22](PF6)Cl, [Ni·12](PF6)Cl and [Ir·1Cl3] are also presented. All of the complexes displayed non-classical triazolyl C–HCl− hydrogen bonding. All but one complex showed no metal-based luminescence at room temperature, while all of the Pt(II) complexes displayed luminescence at 77 K. The electrochemistry of the Ru(II) complexes was also studied and these complexes were found to have higher oxidation potentials than analogous compounds. The redox behaviour of [RuL2]2+ complexes with both 1 and 2 was nearly identical, while [Ru·1Cl2(DMSO)] was oxidised at significantly lower potential. We also show that the Ru(II) complex of 2, [Ru·22](PF6)Cl, gave rise to the formation of a metallo-supramolecular gel, the morphology of which was studied using scanning electron and helium ion microscopy
PUBLISHED
Keywords: 2,6-Bis(1,2,3-triazol-4-yl)pyridine; 2,6-Bis(1,2,3-triazol-4-yl)pyridine; Nanoscience & Materials